2022
DOI: 10.5430/cns.v11n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Nurse students’ views of factors that increase or decrease the attractiveness of the nursing profession

Abstract: Objective: This qualitative study provides up-to-date knowledge about today’s nursing students’ views and experiences of factors that can increase or decrease the attractiveness of nursing and presents students’ ideas for improving the nursing profession.Methods: Data were collected from 168 nursing students at the University of Applied Sciences in Finland through an online survey in March 2022. Inductive content analysis was used to analyze the data.Results: According to the students, the attractiveness of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Professional factors were given less importance, with a mean of 1.91. According to a study conducted by Salminen-Tuomaala and Herttuala in 2023, elements that could increase the appeal of the nursing profession include the need to evolve the social image of the profession, redefine the roles of nurses at various levels (individual, organizational, and societal), and emphasize the value and significance of nursing tasks ( Salminen-Tuomaala & Herttuala, 2023 ). Unlike the results of the present study, the research conducted by Khajeali in 2015 found that social factors such as “family encouragement to study nursing” and “the social status of the nursing profession” were the least important, with means of 2.94 and 2.86, respectively ( Khajeali, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Professional factors were given less importance, with a mean of 1.91. According to a study conducted by Salminen-Tuomaala and Herttuala in 2023, elements that could increase the appeal of the nursing profession include the need to evolve the social image of the profession, redefine the roles of nurses at various levels (individual, organizational, and societal), and emphasize the value and significance of nursing tasks ( Salminen-Tuomaala & Herttuala, 2023 ). Unlike the results of the present study, the research conducted by Khajeali in 2015 found that social factors such as “family encouragement to study nursing” and “the social status of the nursing profession” were the least important, with means of 2.94 and 2.86, respectively ( Khajeali, 2015 ).…”
Section: Discussionmentioning
confidence: 99%